The association of diabetes literacy with self-management among older people with type 2 diabetes mellitus: a cross-sectional study - Utami Rachmawati; Junaiti Sahar; Dwi Nurviyandari Kusuma Wati (BMC, 2019)
Abstract Background Diabetes has become one of public health problem up until now. As the disease progressed, it might lead to increasing complication as well as death related to them. Diabetes as chronic disease in older people can lead to more vulnerable conditions if they fail to carry out a proper diabetes self-management. Diabetes literacy is an internal factor affecting how the older people go about their diabetes management routines. This study aimed to describe diabetes literacy of the older people and identify the relation of diabetes literacy to diabetes self-management of the older people with T2DM in selected areas of Depok City, West Java, Indonesia. Method A cross-sectional observational study was utilized and used 106 samples of older people individuals with T2DM, all of whom were chosen via cluster sampling. This research took place in five selected areas under the supervision of three public health center in Depok City. The data were analyzed using a bivariate t-independent test, the Pearson product-moment correlation, and logistic regression for multivariate analysis to determine the relationship of independent and dependent variable. Result This research shows a significant correlation between diabetes literacy and diabetes self-management (p = 0,011). Conclusion Diabetes self management is associated with diabetes literacy in older people with type 2 diabetes mellitus. Diabetes literacy should be considered when assessing and addressing diabetes-specific health education needs.